Reliability Study and Thermal Performance of LEDs on Molded Interconnect Devices (MID) and PCB - Mahdi Soltani; Moritz Freyburger; Romit Kulkarni; Rainer Mohr; Tobias Groezinger; Andre Zimmermann (IEEE Access, 2018)
Light-emitting diodes (LEDs) have increasingly replaced conventional lamps in the fields of general lighting and consumer electronics. In addition to the sharp price fall, this is also due to the significantly higher energy efficiency and the smaller, more compact design. Recently, their robustness and reliability have also reached a level of quality that surpasses the characteristics of conventional light sources such as halogen and fluorescent lamps. Characteristics, such as excellent design freedom and the possibility for functional integration, highlight the main qualities of molded interconnect devices (MIDs). The use of this technology does not only open doors to extend the application field of LEDs to new products but also presents challenges to the lighting industry. There are many studies dealing with the reliability of LEDs as well as with the usability of the MID technology in different fields. But, the lack of experience from the manufacturers regarding the behavior of this interesting configuration (LED/MID) over the entire life cycle prevents this technology from establishing and consolidating its existence. As LEDs in the automotive sector, especially within headlamps, assume increasingly powerful lighting tasks and are no longer used exclusively for signal transfer or for displays, thermal properties of the substrate materials and the thermo-mechanical behavior of the assembly are particularly relevant. In this context, this paper presents a deep and detailed reliability investigation of this system (LED/MID) and examines the influence of the MID substrate choice on the long-term performance of the LED. The impact of the forward current and of the ambient temperature on the junction temperature of the LED is a proven fact. Therefore, the MID effect was inspected under different operating conditions based on infrared thermography. After analyzing the occurred failure mechanisms, by means of X-ray analysis, thermal transient testing and microscopy, the resulting lifetime model is also presented and discussed.